766 A Review of Toleration of Pnuemocystis Carinii Pneumonitis (PCP) Prophylaxis Treatment in Children with Acute Lymphoblastic Leukaemia. (October 2012) - O'Hare, PM; Moody, A; Zerb, T; Lancaster, D
Abstract : Background and Aims: According to the UKALL2003 protocol, co-trimoxazole should be used as first line therapy to prevent PCP pneumonia, and in cases of intolerance, dapsone or pentamidine can be used as alternative treatment options. Methods: Retrospective review of patient notes and electronic patient records, for those patients who have completed treatment for Acute Lymphoblastic Leukaemia on the UKALL2003 protocol at the Royal Marsden Hospital. Results: 164 patients were commenced on co-trimoxazole, and one was commenced on dapsone. 22(13.4%) of patients did not tolerate co-trimoxazole, with 20 cases of intolerance secondary to cytopenia. Of the 22 patients who discontinued co-trimoxazole, 20 patients (87%) have documentation of G6PD status being investigated, all of whom were negative for G6PD deficiency. The first 5 patients to require 2nd line therapy were commenced on pentamidine, with 'cytopenia' cited as the cause of co-trimoxazole intolerance for all of these patients. One patient was subsequently changed onto dapsone. 17 patients were commenced on dapsone as 2nd line therapy for PCP prophylaxis, with 'cytopenia' cited as the cause of co-trimoxazole intolerance in 15 patients. 5 of the 17 patients who were commenced on dapsone as 2nd line treatment, did not tolerate dapsone. Of these five patients, one had persistent neutropenia, two developed methaemaglobinaemia, and two developed dapsone syndrome. Only one of 165 patients was suspected of developing pneumocystis pneumonia, and retrospectively this patient was found to be non-compliant with co-trimoxazole. Conclusions: Current PCP prophylaxis treatments are effective, and for the majority of patients, co-trimoxazole is well tolerated.